2021
DOI: 10.1002/jgm.3372
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA IGF2‐AS promotes the osteogenic differentiation of bone marrow mesenchymal stem cells by sponging miR‐3,126‐5p to upregulate KLK4

Abstract: Background Osteoporosis (OP) is a bone disease characterized by reduced amount and quality of bone. This study was designed to explore the role and mechanism of lncRNA IGF2‐AS in the osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs). Methods Human lncRNA and miRNA microarray analyses were performed to measure the differential expression levels of lncRNAs and miRNAs in undifferentiated and osteogenically differentiated BMSCs. lncRNA IGF2‐AS, miR‐3,126‐5p, and KLK4 levels were measured by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…LncRNAs regulate osteogenic differentiation; thus, they are important for the development of OP [ 31 ]. For example, Tang et al showed that lncRNA IGF2-AS promotes osteogenic differentiation of hMSCs as evidenced by increased ARS staining and levels of ALP, osterix (Osx), OCN, and RUNX2 [ 32 ]. Several studies have revealed that LINC00205 is involved in the regulation of various biological functions in cells.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs regulate osteogenic differentiation; thus, they are important for the development of OP [ 31 ]. For example, Tang et al showed that lncRNA IGF2-AS promotes osteogenic differentiation of hMSCs as evidenced by increased ARS staining and levels of ALP, osterix (Osx), OCN, and RUNX2 [ 32 ]. Several studies have revealed that LINC00205 is involved in the regulation of various biological functions in cells.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating researches have unveiled the critical roles of lncRNAs in osteogenic differentiation of HBMSCs [ 36 ]. For example, lncRNA IGF2-AS enhances osteogenic differentiation of HBMSCs by targeting miR-3126-5p/KLK4 [ 37 ;] lncRNA XIST inhibits the osteogenic differentiation of HBMSCs [ 38 ]. Here, we selected USP2-AS1 as our research target due to its significant up-regulation in HBMSCs after osteogenic differentiation, according to the results of bioinformatics analysis and RT-qPCR.…”
Section: Discussionmentioning
confidence: 99%
“…In the Decoy mode, lncRNA blocks the effects of transcription factors and regulates the transcription of downstream genes by binding to transcription factors. In addition, lncRNA is rich in miRNA binding sites due to its homology with mRNA, which acts as a miRNA sponge in cells, alleviating the inhibitory influence of miRNA on its target gene and increasing target gene expression [ 11 ]. LncRNA combines with transcription factors, locating the transcription complex on specific DNA sequences in the Guide mode, thereby mediating the binding of transcription factors to specific DNA sequences [ 12 ].…”
Section: The Overview Of Long Non-coding Rnamentioning
confidence: 99%
“…When overexpressed lncRNA SNHG14, the crosstalk balance with miR-185-5p network will be broken, resulting in the increase of WISP2 expression for a better osteogenic effect. LncRNA IGF2-AS functioned as a sponge of miR-3126-5p to regulate KLK4 expression and positively modulated osteogenesis [ 11 ]. Previous studies also have shown that the stable expression of miR-138 or miR-145 decreases bone regeneration, but Linc-ROR can increase ZEB2 expression to enhance the process by acting as competitive endogenous RNAs for miR-138 and miR-145 [ 49 ].…”
Section: The Research Status Of Lncrnas Related To Osteogenic Differe...mentioning
confidence: 99%